The Role of Sharia Supervisory Board in Implementing Public Trust on Sharia Banks - Illa Susilawati; Lutfi Madani; Sutrisno Sutrisno; Arim Nasim; Caria Ningsih (Perhimpunan Intelektual Muslim Indonesia, 2023)
This study aims to see how implementing the Sharia Supervisory Board and its impact on providing public trust in Islamic banks. This study uses a quantitative approach with the method of Systematic Literature Review from various journals. With the Systematic Literature Review method, the research identifies all empirical evidence, where the identification aims to answer questions such as